2022
DOI: 10.2174/1567202619666220406092532
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Changes in Carotid Stenosis Patients After Stenting Detected by Swept-source Optical Coherence Tomography Angiography

Abstract: Background: Carotid artery stenosis (CAS) patients show reduced blood flow in the ophthalmic artery. This study aimed to assess the changes in the choriocapillaris and choroidal thickness in patients with unilateral carotid artery stenosis after carotid stenting using swept-source optical coherence tomography (SS-OCT)/swept-source optical coherence tomography angiography (SS-OCTA). Methods: Fifty-three mild to moderate CAS patients and 40 controls were enrolled in this study. All participants underwent digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Sayin et al [ 21 ] showed significantly decreased choroidal thickness in CAS, while Rabina et al showed no significant difference in choroidal thickness of CAS patients compared to controls. In our study, we showed reduced CVV in ipsilateral eyes compared to contralateral eyes which is in line with our previous report [ 26 ]. Reduced choroidal vascular volume in the ipsilateral eyes may be linked with hypoperfusion due to irregularities in the choroidal blood flow; this may influence the functionality of the microvascular network which may induce a reduced blood flow pressure, ultimately resulting in the choroidal thinning [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sayin et al [ 21 ] showed significantly decreased choroidal thickness in CAS, while Rabina et al showed no significant difference in choroidal thickness of CAS patients compared to controls. In our study, we showed reduced CVV in ipsilateral eyes compared to contralateral eyes which is in line with our previous report [ 26 ]. Reduced choroidal vascular volume in the ipsilateral eyes may be linked with hypoperfusion due to irregularities in the choroidal blood flow; this may influence the functionality of the microvascular network which may induce a reduced blood flow pressure, ultimately resulting in the choroidal thinning [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…To date, very little is known about the impact of carotid stenosis on choroidal circulation. Previous OCTA reports [ 16 , 26 ] did not find any significant difference in the choriocapillaris (the capillaries of the choroid) before and after stenting in CAS patients; the authors suggested changes seen in the choriocapillaris may be irrelevant in the choroid resulting in the insignificant differences. Similarly, our current report did not find a significant difference in the CVI of ipsilateral eyes compared to contralateral eyes.…”
Section: Discussionmentioning
confidence: 82%